Nanophotonic method for polycyclic aromatic hydrocarbons detection in water solutions - Sushko, O. A.; Bilash, О. М.; Rozhitskii, M. M. (Eurosvit, 2013)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental agents commonly believed to contribute significantly to human cancer pathologies. One of the most dangerous organic PAHs carcinogens is benzo[a]pyrene (BP). Like many other carcinogens, PAHs are metabolized enzymatically to various metabolites, some of which are highly reaction active. Proposed nanophotonic analytical method is based on the process of QDs transfer to ionic forms in an EC process and their subsequent reactions with oppositely charged ionic forms of the analyte – PAHs (BP) inside ECL cell, resulting in the formation of emitter and emission of an analytical optical signal.
Keywords: nanophotonic method; polycyclic aromatic hydrocarbons; water solution